A portable medical monitoring device application - Tan, Kean Hwee. (2013)
In this project, we will look at how medication adherence is affecting the healthcare industry and how people are using the technology to solve the problem. Since most of us with smartphones carry the device with us everywhere we go, we can make use of this habit to tackle the problem. On top of that, the growing trend of smartphone users will only lead to more people being exposed to the solution.